Sustainability considerations are not influencing meat consumption in the US - Downs, Shauna M.; Merchant, Emily V.; Sackey, Joachim; Fox, Elizabeth L.; Davis, Claire; Fanzo, Jessica (Elsevier, 2024)
The consumption of animal-source foods, and particularly red meat from ruminants, is a major contributor to greenhouse gas emissions, freshwater use, and loss of biodiversity. Reducing red meat consumption has been identified as a key strategy to mitigate climate change; however, little is known about how to effectively intervene to promote its reduction in the United States (US). This study aimed to examine meat (red, unprocessed, and poultry) and seafood consumption patterns, the factors influencing their consumption (including a reduction in their consumption over time), and how these differed based on socioeconomic variables. The study was conducted through an online survey with a representative sample of the US population (n = 1224) in 2021 using KnowledgePanel®. Overall, we found that most participants reported consuming red meat (78%), processed meat (74%), or poultry (79%) 1–4 times per week, with several differences in consumption patterns based on socio-demographic characteristics. A substantial proportion of the population reported reducing their red (70%) and processed meat (64%) consumption over the previous year, which was much higher than those that reported reducing poultry (34%) or seafood (26%). Key factors influencing red meat reduction were health and price, while environmental sustainability and animal welfare were less important, particularly among certain socio-demographic groups. These findings can help provide insight into how best to frame messaging campaigns aimed at shifting red meat consumption in the US to support climate change mitigation. Focusing on the factors that resonate more with consumers is more likely to lead to shifts in consumption patterns.